Correction: Wang, M., et al. HSP70-eIF4G interaction promotes protein synthesis and cell proliferation in hepatocellular carcinoma. Cancers 2020, 12, 2262 - Wang, Meng; Wei, Kai; Qian, Baifeng; Feiler, Svenja; Murtha-Lemekhova, Anastasia; Büchler, Markus W.; Hoffmann, Katrin (Cancers, 2020)
The authors wish to make the following corrections to this paper [...]
Gesehen am 13.01.2021